Strategic planning of sustainable integrated biofuel and petroleum fuel supply chains - Aba, Michael Moses (2020)
Petroleum has been the major source of meeting the world\'s energy and chemical needs but rising energy demand, dwindling petroleum resources and climate change have led to an energy revolution resulting in the development of alternative fuels to replace fossil-derived energy products. Biofuel is one of the viable solutions that is increasingly becoming part of the energy mix of many nations whose market has become established by biofuel policies and regulations. However, investments in biofuel supply chains can be expensive and several supply chain models have been developed to demonstrate its cost-effectiveness or profitability without considering integrating with existing petroleum infrastructure. Also, seldom considered is the impact of demand fluctuations on capacity allocation and changes over time. Hence, this work presents a multi-period multiscale strategic planning model for policy-decision makers and which is an integrated biofuel and petroleum supply chain which composes a superstructure that combines the components of the biofuel and petroleum supply chain. The model presented is a Mixed Integer Linear Programming (MILP) model used to make strategic and tactical decisions for biorefineries and distribution centers under environmental considerations to ensure sustainability. Furthermore, a dynamic capacity strategy is incorporated which allows for flexibility in the capacity allocation and location decisions in response to demand fluctuations over time. The model is applied to a case study in the Northeast of Brazil under the RenovaBio program where investments in biorefineries are required to overcome the production deficit in the region and eliminate import. Results of the case study carried out produced an optimal facility configuration of biorefineries and distribution centers, the evolution of capacities over time, capacity utilization profile, material flows and inventories, carbon credit and emissions profile from the network while maximizing the net present value of the supply chain. Results also show significant investments in corn dry mill and flex mill plants. This contribution shows that biorefinery supply chains modelled to incorporate the interactions petroleum fuel supply chain can provide insights that would not be possible with only biofuel supply chain models. It is shown that mathematical programming offers useful tools for biorefinery supply chain studiesPetroleum has been the major source of meeting the world\'s energy and chemical needs but rising energy demand, dwindling petroleum resources and climate change have led to an energy revolution resulting in the development of alternative fuels to replace fossil-derived energy products. Biofuel is one of the viable solutions that is increasingly becoming part of the energy mix of many nations whose market has become established by biofuel policies and regulations. However, investments in biofuel supply chains can be expensive and several supply chain models have been developed to demonstrate its cost-effectiveness or profitability without considering integrating with existing petroleum infrastructure. Also, seldom considered is the impact of demand fluctuations on capacity allocation and changes over time. Hence, this work presents a multi-period multiscale strategic planning model for policy-decision makers and which is an integrated biofuel and petroleum supply chain which composes a superstructure that combines the components of the biofuel and petroleum supply chain. The model presented is a Mixed Integer Linear Programming (MILP) model used to make strategic and tactical decisions for biorefineries and distribution centers under environmental considerations to ensure sustainability. Furthermore, a dynamic capacity strategy is incorporated which allows for flexibility in the capacity allocation and location decisions in response to demand fluctuations over time. The model is applied to a case study in the Northeast of Brazil under the RenovaBio program where investments in biorefineries are required to overcome the production deficit in the region and eliminate import. Results of the case study carried out produced an optimal facility configuration of biorefineries and distribution centers, the evolution of capacities over time, capacity utilization profile, material flows and inventories, carbon credit and emissions profile from the network while maximizing the net present value of the supply chain. Results also show significant investments in corn dry mill and flex mill plants. This contribution shows that biorefinery supply chains modelled to incorporate the interactions petroleum fuel supply chain can provide insights that would not be possible with only biofuel supply chain models. It is shown that mathematical programming offers useful tools for biorefinery supply chain studies